Fractures of the facial skeleton - Perry, Michael (Surgeon); Brown, Andrew (Andrew K.); Banks, Peter, 1936- (Wiley-Blackwell, 2015)
Fractures of the Facial Skeleton, Second Edition gives a clear, concise and practical overview of the management of maxillofacial injuries. This new edition has been fully updated to include recent developments and improvements in facial trauma management, with expanded sections on emergency and early treatment, soft tissue injuries and major maxillofacial injuries. Written by an experienced author team, this text will appeal to trainees in all surgical specialities involved in facial trauma. Summary tables and colour illustrations throughout aid understanding, making this both an ideal introduction to the subject and a useful exam revision text. Key features include: -New, updated edition of a well-respected text -Easy-to-read, practical clinical handbook -Covers aetiology and anatomy, emergency management of trauma, imaging, treatment of dentoalveolar, mandible and midfacial injuries, postoperative care, and complications -Suitable for postgraduate students, trainees and practitioners in oral and maxillofacial surgery and practitioners of other medical disciplines involved in facial trauma.